Digitalization and Resilience : Firm-level Evidence During the COVID-19 Pandemic - Abidi, Nordine (IMF Working Papers; Working Paper ;, 2022)
The COVID-19 pandemic has resulted in an unprecedented shock to firms with adverse consequences for existing productive capacities. At the same time, digitalization has increasingly been touted as a key pathway for mitigating economic losses from the pandemic, and we expect firms facing digital constraints to be less resilient to supply shocks. This paper uses firm-level data to investigate whether digitally-enabled firms have been able to mitigate economic losses arising from the pandemic better than digitally-constrained firms in the Middle East and Central Asia region using a difference-in-differences approach. Controlling for demand conditions, we find that digitally-enabled firms faced a lower decline in sales by about 4 percentage points during the pandemic compared to digitally-constrained firms, suggesting that digitalization acted as a hedge during the pandemic. Against this backdrop, our results suggest that policymakers need to close the digital gap and accelerate firms' digital transformation. This will be essential for economies to bounce back from the pandemic, and build the foundations for future resilience.